Exercise during pregnancy protects adult mouse offspring from diet-induced obesity. Issue 1 (December 2015) - Wasinski, Frederick; Bacurau, Reury; Estrela, Gabriel; Klempin, Friederike; Arakaki, Aline; Batista, Rogerio; Mafra, Fernando; Nascimento, Lucas; Hiyane, Meire; Velloso, Lício; Câmara, Niels; Araujo, Ronaldo
Abstract Background Physical exercise induces positive alterations in gene expression involved in the metabolism of obesity. Maternal exercise provokes adaptations soon after birth in the offspring. Here, we investigated whether adult mouse offspring of swim-trained mothers is protected against the development of the deleterious effects of high fat diet (HFD). Methods Our study comprises two parts. First, female C57BL/6 mice were divided into one sedentary and one swim-trained group (before and during pregnancy, n = 18). In the second part, adult offspring (n = 12) of trained and sedentary mothers was challenged to HFD for 16 weeks. Notably, most of the analysis was done in male offspring. Results Our results demonstrate that maternal exercise has several beneficial effects on the mouse offspring and protects them from the deleterious effects of HFD in the adult. Specifically, swimming during pregnancy leads to lower birth weight in offspring through 2 months of age. When subjected to HFD for 4 month in the adulthood, our study presents novel data on the male offspring's metabolism of trained mothers. The offspring gained less weight, which was accompanied by less body fat, and they used more calories during daytime compared with offspring of sedentary mothers. Furthermore, we observed increased adiponectin expression in skeletal muscle, which was accompanied by decreased leptin levels and increased insulin sensitivity. Decreased interleukin-6 expression and increased peptide PYY levels were observed in sera of adult offspring of mothers that swam during pregnancy. Conclusions Our results point to the conclusion that maternal exercise is beneficial to protect the offspring from developing obesity, which could be important for succeeding generations as well.